HUBUNGAN SELF REGULATED LEARNING DENGAN KECURANGAN AKADEMIK MAHASISWA - Wahyu Bintoro; Edy Purwanto; Dyah Indah Noviyani (Educational Psychology Journal, 2013)
Academic cheating is increasing from year to year. Academic fraud will be a negative impact on the perpetrators, both morally, psychologically, and socially. Therefore, it takes a student self regulation, and time management for students facing difficulties in achieving the learning objectives so as to minimize the occurrence of academic fraud on the students, this is related to self- regulated learning. This study aimed to determine the relationship between self-regulated learning (X) with academic cheating (Y) in the Faculty of Education Psychology student Semarang State University. This study is correlational. The population in this study were students of Psychology Faculty of Education Semarang State University class of 2008 - 2011. The population was 380 students. The number of samples in this study were 110 students, sampling techniques used are techniques such as Simple Random Sampling Probability Sampling, which is taking members of the sample population was randomly without regard to the existing strata in the population. The research data were taken using a scale of academic fraud and self-regulated learning scale. The method of data analysis used by the Product Moment Correlation. The researchers concluded that the results showed a negative relationship between self-regulated learning with academic cheating is not proven.